2017
DOI: 10.1111/joms.12260
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Spanning Activities of Corporate HQ Executives Insights from a Longitudinal Study

Abstract: What are the boundary spanning activities undertaken by the Corporate Headquarters (HQ) executives of a Multinational Corporation? We address this question through a five‐year longitudinal case study of one company as it shifted from a traditional HQ in one location, to a dual HQ in two locations, to a virtual HQ split across multiple locations. By observing how HQ executives prioritized their time over the course of this transition, we identified four generic boundary spanning activities: two (spearheading an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 104 publications
(187 reference statements)
2
96
0
3
Order By: Relevance
“…However, when bicultural immigrants distance themselves from their home country identity, they tend to hinder collaborators by micromanaging, narrowing communication channels, and suppressing input. These studies (Birkinshaw et al, ; Kane and Lavina, ) suggest that even though boundary spanning can be an organizational capability, individual actors play a critical role in development of such a capability.…”
Section: Discussionmentioning
confidence: 99%
“…However, when bicultural immigrants distance themselves from their home country identity, they tend to hinder collaborators by micromanaging, narrowing communication channels, and suppressing input. These studies (Birkinshaw et al, ; Kane and Lavina, ) suggest that even though boundary spanning can be an organizational capability, individual actors play a critical role in development of such a capability.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have shown that headquarters activities are geographically dispersed and configured in increasingly complex ways. Large firms (e.g., General Electric, IBM, Lenovo, and Royal Dutch Shell) have disaggregated and dispersed their financial, legal, and managerial headquarters activities across different locations [33][34][35]. Pan (2003) investigated the relocation of the headquarters of listed firms from 2001 to 2012 in China and found that Beijing and Shanghai were the most attractive cities for inter-province relocation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Related to this point, the cross-sectional nature of our study was limiting our analysis and future research should investigate the antecedents of dual headquarters involvement prior to measuring the involvement itself and subsequently look at the outcomes of it (see e.g. the recent longitudinal study of boundary spanning activities of corporate headquarters by Birkinshaw et al 2017). Third, while we contend that subsidiary innovation projects offer a fertile testing ground for the furthering of theory on the nature of the headquarters, the sample of innovations under study ran the risk of being successful, i.e., there is a risk under-sampling of failure (Denrell 2003).…”
Section: Discussionmentioning
confidence: 99%